Facts and figures : basic reading practice with answers - Ackert, Patricia. (Luyện kỹ năng đọc tiếng Anh. Tập 1., 2000)
Animals; How? Why?; Plants; Popular music; Occupations; Interesting People of the World; Exploration and Adventure.